2020
DOI: 10.1101/2020.07.17.20155150
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Trans-omics Landscape of COVID-19

Abstract: System-wide molecular characteristics of COVID-19, especially in those patients without comorbidities, have not been fully investigated. We compared extensive molecular profiles of blood samples from 231 COVID-19 patients, ranging from asymptomatic to critically ill, importantly excluding those with any comorbidities. Amongst the major findings, asymptomatic patients were characterized by highly activated anti-virus interferon, T/natural killer (NK) cell activation, and transcriptional upregulation of inflamma… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
7
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 90 publications
7
7
2
Order By: Relevance
“…Actually, we observed a severity‐dependent decrease in PC species with long and polyunsaturated acyl chains, as shown in Figure 3F,G. PC and LPC reflected and predicted the maximum disease severity, which is concordant with the results of previous studies 26,27 . Regarding the LPS/PS axis, although the PS levels could not be properly evaluated using serum samples (Figure S1), some LPS levels, such as 16:0 LPS and 18:0 LPS, decreased during the early phase, while 22:6 LPS increased during the late phase (Figure S8B,C and Figure 4E).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Actually, we observed a severity‐dependent decrease in PC species with long and polyunsaturated acyl chains, as shown in Figure 3F,G. PC and LPC reflected and predicted the maximum disease severity, which is concordant with the results of previous studies 26,27 . Regarding the LPS/PS axis, although the PS levels could not be properly evaluated using serum samples (Figure S1), some LPS levels, such as 16:0 LPS and 18:0 LPS, decreased during the early phase, while 22:6 LPS increased during the late phase (Figure S8B,C and Figure 4E).…”
Section: Discussionsupporting
confidence: 89%
“…Regarding glycerophospholipids, for the LPC/PC axis, we observed a decrease in LPC in COVID‐19 subjects with mild disease, while an increase in PC was seen in COVID‐19 subjects with severe disease. Previous studies reported lower LPC levels, 17,23,26 while several reports have shown higher LPC levels 20,21 . Some reports showed that subjects with severe disease reportedly had lower LPC levels, 17,26 whereas one paper reported the opposite 21 .…”
Section: Discussionmentioning
confidence: 93%
“…patient OMICS data, including proteomics and transcriptomics regulation of whole blood, serum or plasma of mostly inpatients (10; 12; 13; 22; 57; 63; 71; 95)…”
Section: Methodsmentioning
confidence: 99%
“…We recapitulate human RBPs which are predicted or experimentally determined to binding to SARS-CoV-2 by previous studies and identify novel host RBP candidates with no previously reported binding to SARS-CoV-2. We integrate knowledge of these proteins across other pathogens and highlight RBPs with clinical relevance, by annotating those that were found among SARS-CoV-2-associated genes from Genome Wide Association Studies (GWAS) (64), CRISPR studies (24; 30; 70; 91), physical binding experiments (18; 69; 89), or patient OMICS data from blood serum and plasma (10; 12; 13; 22; 57; 63; 71; 95). Finally, we perform extensive in silico single-nucleotide perturbations across the SARS-CoV-2 genome to identify variants that would lead to gain and/or disruption of RBP binding sites and thus may alter viral fitness.…”
Section: Introductionmentioning
confidence: 99%
“…Chaoyang Sun 1,2 Yong Bai 3 Dongsheng Chen 3 Liang He 1,2 Jiacheng Zhu 3,4 Xiangning Ding 3,4 Lihua Luo 3,4 Yan Ren 3 Hui Xing 5 Xin Jin 3,6,7 Gang Chen…”
Section: O N F L I C T O F I N T E R E S Tmentioning
confidence: 99%